'If I only had a little humility, I would be perfect': Children's and adults' perceptions of intellectually arrogant, humble, and diffident people. Issue 1 (2nd January 2017) - Hagá, Sara; Olson, Kristina R.
Abstract: Intellectual humility is usually regarded as a virtue. In this paper, we conceptualized intellectual humility along two dimensions: (1) placing an adequate level of confidence in one's own beliefs; (2) being willing to consider other people's beliefs. We tested whether children (ages 4 to 11 years) and adults perceived intellectual humility as positive and how these perceptions changed across development. To do so, we asked participants to evaluate an intellectually humble person as compared to an intellectually arrogant person, who readily dismissed other people's beliefs, or to an intellectually diffident person, who was unsure of a well-supported belief. Young children did not favor the intellectually humble person over the others, but older children and adults liked this person better and tended to consider her nicer than the arrogant one and smarter than the diffident one. These findings suggest that the virtuousness of intellectual humility in others is recognized from mid-childhood on.